LINGUOPOETIC CHARACTERISTICS OF PARENTHESES IN THE WORKS OF ERKIN AZAM - Shoirakhan Toshkhujaeva Ganievna (Galaxy International Interdisciplinary Research Journal, 2022)
In per the parantez case and their study in modern uzbek linguistics were explored. In addition, in Erkin A’zam works parantez was analyzed and their lingvopoetic investigation were showed. In terms of given feature of the works the writer aim and his achievement into modern uzbek linguistics were evaluated.